Investigating the effect of self-evaluation by checklist in learning the principles of drug injection and the satisfaction of nursing students in the pharmacology internship at Zanjan College of Nursing and Midwifery - Ali Imani; Atefeh Vaezi; Fatemeh Moradi (Mashhad University of Medical Sciences, 2024)
Background: Among the various assessment tools for learning, self-evaluation is an efficient method that enables students to reflect on their learning. The present study was conducted with the aim of determining the effectiveness of self-evaluation by checklist in learning the principles of drug injection and the satisfaction of nursing students in the pharmacology internship in 2022 at Zanjan College of Nursing and Midwifery.Method: The present study was a quasi - experimental study that was conducted as a case-control study in the pharmacology internship unit on 36 students. In the case group (18 participants), each student completed the checklist 3 times in the presence of the instructor, after administering the drug, in three consecutive days. But in the control group, only the instructor, like the case group, completed the drug administration checklist. At the end of the internship, the satisfaction level of the students of both groups was measured by a satisfaction questionnaireResults: 55.56% of the students in the case group were male and 55.56% of the students in the control group were female. The mean and standard deviation of learning on the second and third day were respectively 11.44±1.68 and 14.78±0.548 in the case group and 8.78±1.26 and 8.00±1.45 in the control group, which was statistically significant (p=0.000). There was no significant difference in the level of satisfaction in the two groups.Conclusion: The use of self-evaluation method had a significant effect in training drug administration skills.